Dietary strategies to mitigate alzheimer's disease: insights into antioxidant vitamin intake and supplementation with microbiota-gut-brain axis cross-talk - Wan Zurinah, Wan Ngah; Hajar Fauzan, Ahmad; Sheril June, Ankasha; Suzana, Makpol; Tooyama, Ikuo (MDPI AG, 2024)
Alzheimer's disease (AD), which is characterized by deterioration in cognitive function and neuronal death, is the most prevalent age-related progressive neurodegenerative disease. Clinical and experimental research has revealed that gut microbiota dysbiosis may be present in AD patients. The changed gut microbiota affects brain function and behavior through several mechanisms, including tau phosphorylation and increased amyloid deposits, neuroinflammation, metabolic abnormalities, and persistent oxidative stress. The lack of effective treatments to halt or reverse the progression of this disease has prompted a search for non-pharmaceutical tools. Modulation of the gut microbiota may be a promising strategy in this regard. This review aims to determine whether specific dietary interventions, particularly antioxidant vitamins, either obtained from the diet or as supplements, may support the formation of beneficial microbiota in order to prevent AD development by contributing to the systemic reduction of chronic inflammation or by acting locally in the gut. Understanding their roles would be beneficial as it may have the potential to be used as a future therapy option for AD patients.